Philippine sanctuary : a Holocaust odyssey - Harris, Bonnie M. (2020)
"Of the many refugee trails filled with stateless Jews fleeing Europe during the decades of the Nazi Regime, the odyssey of Cantor Joseph Cysner's escape from Hamburg to Poland to the Philippines stands unique. Joseph escaped the fate of thousands of refugees held at border-camps along the German-Polish border in 1938 and joined hundreds of European refugee Jews ultimately saved from destruction between 1937 and 1941 by little known rescue plans in the East Asian Community of the Philippines. His rescue by Commonwealth officials President Manual Quezon and High Commissioner Paul V. McNutt, and American Jewish businessmen and leaders in Manila, illuminates their heroic efforts in organizing selection and sponsorship programs that overcame limits imposed by the US and other countries during the refugee crisis and heroically saved as many souls as they could before war intervened. Even though it too was ill-fated by the Japanese invasion, Quezon's remarkable offer demonstrated what could be accomplished when nation's leaders were willing to put aside political agendas to act in the universally noble cause of saving human lives. By opening their doors to the refugees, the Filipinos also opened their hearts and gave them a new homeland. Joseph Cysner's personal story of refuge in the Philippines and the vibrant Jewish community that arose there weaves itself throughout the humanitarian efforts to aid the persecuted with a sanctuary in the Pacific. This book resurrects these important events from historical oblivion